Antioxidant Activity of Date Palm Fruit (Phoenix dactylifera L.) Extract for Oxidative Stabilisation of Butter Oil at Ambient Temperature: Oxidative Stabilisation of Butter Oil by Date Palm Fruit - Rahman, Fazal; Nadeem, Muhammad; Khan, Sabir; Ahmad, Shakeel; Zahoor, Yasir (Biological Sciences - PJSIR, 2015)
In this study, long term preservation of butter oil was achieved through ethanolic extract of date palm fruit (Phoenix dactylifera L.). Butter oil was supplemented with date palm fruit extract (DPFE) at three different concentrations i.e. 250, 500 and 750 ppm (T1, T2 and T3) and compared with a control. Total phenolic content, DPPH free radical scavenging activity and inhibition of linoleic acid peroxidation of the DPFE was 5.19 GAE, 74.2 and 81%, respectively. IC50 value of date extract for the inhibition of DPPH and linoleic acid peroxidation was 2.45 and 0.82 mg/mL, respectively. The loss of oleic acid and linoleic acid in control after six months of storage was 16 and 52% as compared to T3 which was 4% and 14%. T3 yielded the lowest concentration of primary and secondary oxidation products with no effect on sensory attributes. DPFE can be used to enhance the shelf life of butter oil at ambient temperature.